정상인에서 빛간섭단층촬영혈관조영술을 이용한 혈관 밀도 측정: 분석 영역에 따른 차이 - 임종찬(Jong Chan Im) (Daihan angwa haghoi jabji, 2019)
목적: 정상인을 대상으로 빛갑섭단층촬영혈관조영술을 이용하여 분석 영역에 따른 중심오목 주위의 혈관 밀도의 차이를 알아보고자 하였다. 대상과 방법: 정상인 20명을 대상으로 빛간섭단층촬영혈관조영술을 시행하였다. 분석 영역을 3 × 3 mm 영역(Box), Box에서 중심오목무혈관부위(foveal avascular zone, FAZ)를 제외한 영역(Box-FAZ), 직경 3 mm 원 영역(Circle), Circle에서 FAZ를 제외한 영역(Circle-FAZ), 직경 1 mm와 3 mm 동심원 사이의 영역(Ring)으로 설정하고 분석 영역에 따른 혈관 밀도와 FAZ 면적을 측정하였다. 결과: 표층모세혈관총의 혈관 밀도는 Box 34.00 ± 3.97, Box-FAZ 35.37 ± 4.09, Circle 31.70 ± 4.56, Circle-FAZ 33.34 ± 4.72, Ring 35.22 ± 5.09로 차이가 난다(p<0.001). 심부모세혈관총도 Box 30.04 ± 3.51, Box-FAZ 31.59 ± 3.65, Circle 29.49 ± 3.57, Circle-FAZ 31.46 ± 3.72, Ring 32.60 ± 4.00로 차이가 있었다(p<0.001). 표층과 심부 모세혈관총 간 혈관 밀도의 비교는 모든 분석 영역에서 차이가 있었다(각각 p<0.001, p<0.001, p=0.001, p=0.005, p=0.001). 결론: 분석 영역이 다르게 설정되었다면, 빛간섭단층촬영혈관조영술을 이용한 혈관 밀도 결과의 차이가 있었다. 그러므로 연구 결과를 비교할 때 분석 영역이 다르게 설정되었다면 결과 해석에 주의를 요한다. Purpose: To evaluate the vessel density of macula according to analysis area in health subjects using optical coherence tomography angiography (OCTA). Methods: We retrospectively analyzed 30 eyes of 20 healthy people who underwent OCTA. We measured vessel density (VD) according to analysis area and foveal avascular zone (FAZ) size of superficial capillary plexus (SCP) and deep capillary plexus (DCP). The analysis areas were classified as 3 × 3 mm scan area (Box), Box area excluding FAZ (Box-FAZ), fovea centered 3 mm circle area (Circle), Circle area excluding FAZ (Circle-FAZ) and area between fovea centered 1 mm circle and 3 mm circle (Ring). Results: The SCP VDs were Box 34.00 ± 3.97, Box-FAZ 35.37 ± 4.09, Circle 31.70 ± 4.56, Circle-FAZ 33.34 ± 4.72, and Ring 35.22 ± 5.09. The DCP VDs were Box 30.04 ± 3.51, Circle 29.49 ± 3.57, Box-FAZ 31.59 ± 3.65, Circle-FAZ 31.46 ± 3.72, and Ring 32.60 ± 4.00. There was a significant difference according to analysis area from both SCP and DCP (p < 0.001 and p < 0.001, respectively). Comparison of the vessel density between SCP and DCP in the same analysis area were different in all areas (p < 0.001, p = 0.001, p < 0.001, p = 0.005, p = 0.001, respectively). Conclusions: This study shows different results according to analysis area when measuring VD using OCTA. Therefore, when comparing studies related to VD, it is necessary to pay attention to the analysis area in the interpretation of the results. KCI Citation Count: 0